17p11.2 and Xq28 duplication detected in a girl diagnosed with Potocki–Lupski syndrome. (December 2015) - Sumathipala, Dulika; Mandawala, Eranda; Sumanasena, Samanmalee; Dissanayake, Vajira
Abstract Background Potocki–Lupski syndrome is a microduplication syndrome associated with duplication at 17p11.2. Features include facial dysmorphism, moderate to mild cognitive impairment and behavioural abnormalities including autism spectrum disorders. Case presentation We describe a patient from Sri Lanka that was referred for genetic assessment at 4 years of age due to subtle facial dysmorphism and expressive language impairment. She was diagnosed with Potocki–Lupski syndrome through multiplex ligation probe amplification. She carried two duplications; one in 17p11.2 consistent with Potocki–Lupski, and one in Xq including the region for X-linked intellectual disability. Conclusion Despite the absence of expected behavioural symptoms, many features of this patient are in accordance with Potocki–Lupski syndrome. This is the first diagnosed patient in Sri Lanka.